Parathyroid gland detection using an intraoperative autofluorescence handheld imager – early feasibility study - Ali, Khalid Mohamed; Wolfe, Samantha A.; Nagururu, Nimesh V.; Seo, Stefanie; Han, Sung-Min; Kim, Yoseph; Oh, Eugene; Kim, Dong-Yun; Ning, Bo; Lee, Seung Yup; Cha, Richard Jaepyeong; Tufano, Ralph P.; et al. (Frontiers in Endocrinology, 2023)
Introduction: Parathyroid glands may be compromised during thyroid surgery which can lead to hypoparathyroidism and hypocalcemia. Identifying the parathyroid glands relies on the surgeon’s experience and the only way to confirm their presence was through tissue biopsy. Near infrared autofluorescence technology offers an opportunity for real-time, non-invasive identification of the parathyroid glands. Methods: We used a new research prototype (hANDY-I) developed by Optosurgical, LLC. It offers coaxial excitation light and a dual-Red Green Blue/Near Infrared sensor that guides anatomical landmarks and can aid in identification of parathyroid glands by showing a combined autofluorescence and colored image simultaneously. Results: We tested the imager during 23 thyroid surgery cases, where initial clinical feasibility data showed that out of 75 parathyroid glands inspected, 71 showed strong autofluorescence signal and were correctly identified (95% accuracy) by the imager. Conclusions: The hANDY-I prototype demonstrated promising results in this feasibility study by aiding in real-time visualization of the parathyroid glands. However, further testing by conducting randomized clinical trials with a bigger sample size is required to study the effect on levels of hypoparathyroidism and hypocalcemia.